Surat Bupati Cianjur Untuk Raffles (1816): Naskah Melayu Pertama yang Ditulis Menggunakan Aksara Latin - Hazmirullah Aminuddin (Jumantara: Jurnal Manuskrip Nusantara, 2020)
In this article, I discuss a letter from the first Raden Aria Adipati Prawiradireja (regent of Cianjur period 1813-1833) for Thomas Stamford Raffles. The letter, written on 11 Jumadilawal 1231 Hegira (April 9th, 1816), contain farewell speech to Raffles who have just finished his six-years service as Lieutenant-Governor Java and It's Dependencies. This letter is a British Library collection and it had been put in a ”bundle” coded Add Ms 45273. The letter interests me because it was written by used Latin script and in the Malay language. In fact, the local rulers in Java, in the second decade of the nineteenth century, usually used the Jawi script (on the Malay language) or the Java script (on the Javanese language) in the letter writing. The research result show that Raden Aria Adipati Prawiradireja was the first indigenous ruler who used the Roman script for writing of Malay language. But, the letter was not the first Malay manuscript that written by using the Latin script. It is because the Roman script has been used at least in the seventeenth century to translate the Bible.